Four distinct regulatory regions of the cut locus and their effect on cell type specification in Drosophila. - Liu, S.; McLeod, E.; Jack, J. (Genetics, 1991)
The cut gene in Drosophila is necessary in at least one cell type, the external sensory organs, for proper cell type specification and morphogenesis. It is also expressed in a variety of other tissues, where its function is less well characterized. Previous work has demonstrated that mutations affecting all the tissues map in the transcribed and translated portion of the gene, while mutations that are tissue specific in their effects map in the 140 kb upstream of the most 5' exon known. Within that 140 kb, the mutations fall into four subregions, two of which contain mutations affecting unique sets of tissues and the other two of which contain mutations that affect a third set. Our examination of the defects of mutants, their complementation behavior, and their effect on the distribution of the cut protein in embryos, alters the picture in three important ways. First, some mutations convert the cells of the Malpighian tubules into what appear to be gut cells, suggesting that cut is necessary for cell type specification and morphogenesis in a variety of tissues. Second, mutations in each of the four subregions in the 140 kb of upstream DNA cause a different set of phenotypes, suggesting that the regulatory region contains at least four separate units with different tissue specific functions. And third, mutations have now been identified that map in the transcribed and translated portion of the gene but that have tissue specific effects.